When does conscious memory become dependent on the hippocampus? The role of memory load and the differential relevance of left hippocampal integrity for short- and long-term aspects of verbal memory performance - Witt, Juri-Alexander; Coras, Roland; Becker, Albert J.; Elger, Christian E.; Blümcke, Ingmar; Helmstaedter, Christoph (Brain Structure & Function, 2019)
Supraspan list learning tests are sensitive measures used to assess temporal lobe dysfunction. Most frequently employed is the Rey Auditory Verbal Learning and Memory Test (RAVLT). The test’s structure is determined by a short- and long-term memory component. During the first of five learning trials, the short-term memory component is the highest and steadily decreases over the following trials, while the long-term memory component concurrently increases and reaches its maximum at the delayed recall after a retention interval of 30 min. The study aimed to test the hypothesis that the functional relevance of left hippocampal integrity for conscious memory rises along with the increasing degree of the long-term memory component. Moreover, we investigated whether classical measures of short-term and working memory are also dependent on the hippocampus. The analysis was based on 37 adult patients who had undergone surgery for left mesial temporal lobe epilepsy. Neuronal cell densities of the resected left hippocampus were correlated with the presurgical memory performance across trials of the VLMT (the German RAVLT) and with digit span and working memory capacity (WMS-R). Whereas digit span and working memory capacity were not related to hippocampal cell counts, there was a significant correlation between left hippocampal integrity and VLMT memory performance, already regarding the first supraspan learning trial. Correlations steadily increased during the learning course. The highest correlation was seen regarding the delayed free recall. The results indicate an increasing correspondence between the integrity of the left hippocampus and verbal memory with an increasing long-term memory component. Immediate recall of verbal material became already dependent on left hippocampal integrity when the verbal memory load exceeded the memory span (supraspan list learning), while classical span measures that assess verbal short-term and working memory were not affected by left hippocampal pathology.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Cell densities; Cornu ammonis; Declarative memory; Dentate gyrus; Hippocampus; Learning; Memory; Neuronal cell counts; Working memory